Modelling distribution of butterflies (Nymphalidae:satyrinae) from secondary records and database in Sarawak - Siti Zakiah, binti Hamid (Universiti Malaysia Sarawak, UNIMAS, 2012)
The study of species diversity of Rhophaloceran species from family Nymphalidae (subfamily: Satyrinae) had been studied by many researchers. Although there was a documentation studied had been done, but the overview on the species distribution are still in the concept of datasheets, while our main objective of modelling distribution of the butterflies family Nymphalidae (subfamily: Satyrinae) is to map current distribution of butterflies from subfamily Satyrinae and identify area(s) with high species diversity. The secondary data were collected from UNIMAS Zoological Museum, Sarawak Museum, and also Sarawak Biodiversity Centre. There is a total of 860 individual collected from 82 species from this subfamily Satyrinae. All of these data were collected from the compilation of 19 sites while the highest number of species collected was from Samarahan (24) with 128 individuals, compared to the lowest species collected at Sri Aman, Sarikei, and Betong with only one species, respectively. Besides that, the Akaike’s Information Criteria (AIC) value has been shown from the analysing data of Generalised Linear Model (GLM). The AIC value will determine the best variable from set of variables and the variable that have the lowest AIC are the best. From the data analysis, the best predictive variables is disturbance effect by having the lowest AIC value of 139.9 compared to the habitat type (142.4) which corresponding to the species distribution of butterflies from subfamily Satyrinae.